L’interaction entre connaissances linguistiques et connaissances extralinguistiques en traduction. Une étude de cas - Künzli, Alexander (HERMES - Journal of Language and Communication in Business, 2005)
This study is a case study. Two professional translators were asked to translate a user guide from French into Swedish while thinking aloud. The focus of the study was on the interaction between their linguistic knowledge and their extralinguistic knowledge as revealed by the translation strategies and principles used by the participants to translate a complex noun phrase. The results show that extralinguistic knowledge can only facilitate the translation process and compensate for a lack of linguistic knowledge if the latter reaches a minimum threshold. A lack of linguistic knowledge cannot either be compensated for by applying translation strategies and principles that have proved successful when the translator is working from a language of which he or she has a better knowledge. Likewise, an education in the ﬁ eld of civil engineering does not amount to the same thing as being able to provide quality in technical translation. The results have potential implications for research and training.